The secret body : how the new science of the human body is changing the way we live - Davis, Daniel M. (Daniel Michael), 1970- (Princeton University Press, 2021)
"A perfect blend of cutting-edge science and compelling storytelling."--Bill Bryson ; A revolutionary new vision of human biology and the scientific breakthroughs that will transform our lives. Imagine knowing years in advance whether you are likely to get cancer, or having a personalized understanding of your individual genes, organs, and cells. Imagine being able to monitor your body's well-being, or have a diet tailored to your microbiome. The Secret Body reveals how these and other stunning breakthroughs and technologies are transforming our understanding of how the human body works, what it is capable of, how to protect it from disease, and how we might manipulate it in the future. Taking readers to the cutting edge of research, Daniel Davis shows how radical new possibilities are becoming realities thanks to the visionary efforts of scientists to reveal the invisible and secret universe within each of us. Focusing on six important frontiers, Davis describes what we are learning about cells, the development of the fetus, the body's immune system, the brain, the microbiome, and the genome-areas of human biology that are usually understood in isolation. Bringing them together here for the first time, Davis offers a new vision of the human body as a biological wonder of dizzying complexity and possibility. Written by an award-winning scientist at the forefront of this adventure, The Secret Body is a gripping drama of discovery and a landmark account of the dawning revolution in human health